TINGKAT PENGETAHUAN DAN KEPATUHAN MASYARAKAT DALAM PENGGUNAAN AMOXICILLIN UNTUK PENGOBATAN SENDIRI DI WILAYAH KELURAHAN LOLU SELATAN KECAMATAN PALU SELATAN - Firdawati Amir Parumpu (As-Syifaa Jurnal Farmasi, 2016)
This study was aimed to determine the Society’s Levels of Knowledge and Compliance in Using Amoxicillin to Self-Medicate in South Lolu Urban Village, South Palu Sub-District. The basis of this study was descriptive survey and descriptive analytical approach aided by frequency table and percentage. Data and material collection was performed using observation, interview accompanied by questionnaire or list of question. The samples in this study were 75 adults in South Lolu Urban Village, South Palu Sub-District who were considered to know the research object, representing a population of 772 households. Based on the research result, it was determined that quite a lot of people in South Lolu Urban Village, South Palu Sub-District didn’t have any knowledge on Amoxicillin, influencing people’s level of compliance to rules of taking amoxicillin. It’s also due to other reasons, such as trying based on people’s recommendation, recovery after self-medicating, and unwillingness to take medicine for a long time. Therefore, socialization was required to support the knowledge of the people of South Lolu Urban Village, South Palu Sub-District to reduce resistance.